PENGARUH LAPORAN KEBERLANJUTAN DAN DIVERSITAS GENDER TERHADAP BIAYA UTANG (Sub Sektor Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2021) (Jurnal Ekonomi dan Bisnis, 2025)
This research is a quantitative exploration which means finding out and investigating how much influence Sustainability Reports and Gender Diversity have on Costs. In this study, a sample of 43 companies included in the Food and Beverage subsector and listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period was used with the purposive sampling method used in sampling. This study also utilizes additional information obtained through the IDX website and company websites. data analysis was carried out using multiple linear regression methods, and hypothesis testing was carried out using the SPSS version 22 application. The first hypothesis shows that sustainability reports have an effect on debt costs with a significance weighted 0.024
Keywords: Sustainability Reporting; Gender Diversity; and Cost Of Debt